How do you evaluate #4( 3+ 1) - 2( 6+ 4)#?

1 Answer
Mar 2, 2018

Answer:

The result is #-4#.

Explanation:

Follow PEMDAS, or the order of operations. PEMDAS stands for:

#"Parentheses"#

#"Exponents"#

#"Multiplication"#

#"Division"#

#"Addition"#

#"Subtraction"#

Here's our expression:

#color(white)=4(3+1)-2(6+4)#

First, simplify the expression in the parentheses:

#color(white)=4(color(red)(3+1))-2(color(blue)(6+4))#

#=4(color(red)4)-2(color(blue)10)#

Next, simplify any exponents. (There are none.) Then, do any multiplication:

#color(white)=color(orange)(4(4))-color(green)(2(10))#

#=color(orange)16-color(green)20#

Lastly, since there isn't any division or addition left, do the final subtraction step:

#color(white)=16-20#

#=-4#

That's the answer!